Macrophages and Dendritic Cells: Partners in Atherogenesis. Issue 4 (19th February 2016) - Cybulsky, Myron I.; Cheong, Cheolho; Robbins, Clinton S.
Abstract : Atherosclerosis is a complex chronic disease. The accumulation of myeloid cells in the arterial intima, including macrophages and dendritic cells (DCs), is a feature of early stages of disease. For decades, it has been known that monocyte recruitment to the intima contributes to the burden of lesion macrophages. Yet, this paradigm may require reevaluation in light of recent advances in understanding of tissue macrophage ontogeny, their capacity for self-renewal, as well as observations that macrophages proliferate throughout atherogenesis and that self-renewal is critical for maintenance of macrophages in advanced lesions. The rate of atherosclerotic lesion formation is profoundly influenced by innate and adaptive immunity, which can be regulated locally within atherosclerotic lesions, as well as in secondary lymphoid organs, the bone marrow and the blood. DCs are important modulators of immunity. Advances in the past decade have cemented our understanding of DC subsets, functions, hematopoietic origin, gene expression patterns, transcription factors critical for differentiation, and provided new tools for study of DC biology. The functions of macrophages and DCs overlap to some extent, thus it is important to reassess the contributions of each of these myeloid cells taking into account strict criteria of cell identification, ontogeny, and determine whether their key roles are within atherosclerotic lesions or secondary lymphoid organs. This review will highlight key aspect of macrophage and DC biology, summarize how these cells participate in different stages of atherogenesis and comment on complexities, controversies, and gaps in knowledge in the field. Abstract : Supplemental Digital Content is available in the text.